1999
DOI: 10.1111/j.1600-0536.1999.tb06030.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory classification of substances oxidized to skin sensitizers on exposure to air

Abstract: Regulatory classification of substances in the European Union (EU) is intended to identify their hazardous toxicological properties in a formal and harmonized manner. In the regulatory work, a specific chemical with its molecular structure is classified as a skin sensitizer. This implies that the compound is stable throughout its lifetime. The purpose of the present paper is to discuss the problem of skin sensitizing oxidation/degradation products formed by air exposure of various materials or substances with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The European Economic Community Cosmetics Directive has set limit values for the maximal concentration of phenylenediamines in hair dyes to 6 % (PPD) and 10 % (PTD), provided that the active dye formulation contains an excess of coupling compounds [18]. The toxicological potential of technical and commercial formulations of aryldiamines is not only coined by the pure compounds themselves but also by side products of their technical synthesis and by chemical (aut)oxidation products formed during post production handling, product formulation, storage, application, or environmental exposure [19]. In contact with air or oxidizing agents like peroxides, phenylenediamines are easily transformed into complex mixtures of monomeric, dimeric, oligomeric, and polymeric oxidation products.…”
Section: Introductionmentioning
confidence: 99%
“…The European Economic Community Cosmetics Directive has set limit values for the maximal concentration of phenylenediamines in hair dyes to 6 % (PPD) and 10 % (PTD), provided that the active dye formulation contains an excess of coupling compounds [18]. The toxicological potential of technical and commercial formulations of aryldiamines is not only coined by the pure compounds themselves but also by side products of their technical synthesis and by chemical (aut)oxidation products formed during post production handling, product formulation, storage, application, or environmental exposure [19]. In contact with air or oxidizing agents like peroxides, phenylenediamines are easily transformed into complex mixtures of monomeric, dimeric, oligomeric, and polymeric oxidation products.…”
Section: Introductionmentioning
confidence: 99%
“…Sunil et al (2007) have shown that young and old mice when exposed to the product of the reaction between limonene and ozone for 3 h show an inflammatory response induction, increasing TNFa, cyclooxygenase-2 and superoxide dismutase in alveolar macrophages. This monoterpene is a potentially sensitizer compound, probably due to the presence of limonene-1,2-epoxide, a product of its oxidation (Karlberg et al, 1999). In contrast, Rolseth et al (2002) showed that limonene-1,2-epoxide was not responsible for the limonene toxicity when investigated in culture of human pulmonary cells.…”
Section: Introductionmentioning
confidence: 85%
“…As reviewed by Karlberg et al (1999) and Downs and Sansom (1999) abietic type acids are easily oxidised when in contact with air, and the oxidation products are thought to be contact sensitisers. Apart from resin acids and esters of resin acids, the non-acidic part of a rosin has provoked positive reactions in human patch testing (Hausen and Mohnert, 1989).…”
Section: Other Studies/contact Sensitisationmentioning
confidence: 99%